Pengaruh NPF, FDR, dan BOPO Terhadap Profitabilitas BTN Syariah - Fatimatuz Zahro, Sri Indah; Ghafur, Abd.; Nasrifah, Maula (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
The purpose of this study is to determine the impact of NPF, FDR, and BOPO on the profitability of BTN Syariah as measured using ROA. This data comes from the BTN Syariah website (www.btn.co.id) which has 36 samples of audited financial statements from 2015 to 2023. The methods used are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results showed that the NPF and BOPO variables had a negative and considerable impact on the ROA variable. While the FDR variable has a large and good impact on the ROA variable. In addition, ROA variables are influenced simultaneously by NPF, FDR and BOPO variables. According to the coefficient of determination, NPF, FDR, and BOPO variables contributed 85.3% to ROA.